2023
DOI: 10.3390/jcs7040150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biobased SiO2 on the Morphological, Thermal, Mechanical, Rheological, and Permeability Properties of PLLA/PEG/SiO2 Biocomposites

Abstract: Nowadays, companies and researchers are concerned about the negative consequences of using synthetic polymers and direct their efforts to create new alternatives such as biocomposites. This study investigated the effect of biobased SiO2 on the properties of poly(L-lactic acid)/SiO2 (PLLA/SiO2) and poly(L-lactic acid)/SiO2/poly(ethylene glycol) (PLLA/SiO2/PEG) composites. The SiO2 was obtained from rice husk incineration and mixed with PLLA at various concentrations (5, 10, and 15 wt.%) via melt extrusion befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…The T m of SPT-5%, 10%, and 15% were 156 • C, which occurred in the second peaks (Figure 3c). The T m of the PLA-TPS was 152 • C. Morales et al [44] found that the melting point of neat PLA is 150 • C. This indicates that SCG can slightly delay the melting of bioplastics.…”
Section: Thermal Analysismentioning
confidence: 95%
See 3 more Smart Citations
“…The T m of SPT-5%, 10%, and 15% were 156 • C, which occurred in the second peaks (Figure 3c). The T m of the PLA-TPS was 152 • C. Morales et al [44] found that the melting point of neat PLA is 150 • C. This indicates that SCG can slightly delay the melting of bioplastics.…”
Section: Thermal Analysismentioning
confidence: 95%
“…Ma et al [55] explained that adhesion of polymers could be enhances if the matrix was higher so that the interaction between the polymers would improve. SCG is a dust particle which can lead to a larger total surface area by adding more matrix, allowing the SCG to have a better bond with another polymer [44]. Based on the statistical data, the addition of 5 and 15% SCG was significantly different, while 10% SCG was not significantly different from 5 and 15% SCG.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Composite materials of various natures attract a growing interest of researchers and industrialists due to their unique properties and wide range of possible applications [1][2][3][4]. In turn, carbon nanomaterials (CNMs) possess high surface area, tailored porous structure, good electrical conductivity, etc.…”
Section: Introductionmentioning
confidence: 99%